Filming the World’s End. Images of the Apocalypse in Lars von Trier’s "Epidemic" and "Melancholia" - Kollig, Danielle Verena (Amaltea. Revista de Mitocrítica, 2013)
Este artículo analiza dos películas de Lars von Trier, Epidemia y Melancolía, atendiendo a su concepción del fin del mundo. Examina si las imágenes apocalípticas de ambas películas se presentan como un espectáculo del que se puede disfrutar o si el fin del mundo aparece como un suceso que produce inquietud. Con este propósito, el artículo examina el decorado, la banda sonora, así como el color de la escenografía de ambas películas. El estudio sostiene que Epidemia y Melancolía presentan distintas concepciones del fin del mundo como forma más radical de apocalipsis. Mientras que Epidemia presenta la extinción de la vida sobre la tierra como un suceso que mueve a la reflexión crítica sobre la participación implícita del público en el proceso, Melancolía concibe el fin del mundo como un acontecimiento sublime que sabe extraer belleza de su composición visual y musical, y deja al espectador sumido en una actitud de recepción más bien pasiva. En este contexto, cobra importancia el concepto de ‘exceso audiovisual’, que no puede aplicarse al caso de Epidemia, mientras que constituye un elemento central en Melancolía. Abstract This article analyzes Lars von Trier’s films Epidemic and Melancholia with regard to their designs of world demise. It examines whether the apocalyptic images the two films refer to are suggested as a spectacle that is to be enjoyed, or whether world demise appears as an occurrence to unsettle. To that extent, the article inspects the films’ settings, their soundtracks, as well as their mise-en-scenes’ coloring. It contends that both Epidemic and Melancholia differ in their designs of world demise as the most definite form of apocalypse. Whereas Epidemic draws an image of the end of life on the world as an occurrence that critically reflects on the audience’s implicit participation in it, Melancholia designs the end of the world as a sublime event that derives beauty out of its musical and visual composition and leaves the audience in a rather passive state of reception. Important in this context becomes the notion of ‘audio-visual excess’, which proves impossible to be applied to Epidemic while being a central element to Melancholia.